OPINI MASYARAKAT KOTA PEKANBARU TENTANG KABUT ASAP KEBAKARAN HUTAN DAN LAHAN DI PROVINSI RIAU TAHUN 2019 - Fikri Efendi; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the opinion of the people of Pekanbaru City about the haze of forest and land fires in Riau Province in 2019 and to find out the prevention and control efforts made by the Riau provincial government against the haze of forest and land fires. This study uses a qualitative method by interviewing 7 informants. The results of this study indicate the tendency of public opinion in Pekanbaru City to contain criticism and hope, contain a counter-direction to the efforts to overcome and prevent the haze of forest and land fires carried out by the Riau Provincial government. Based on the four theoretical factors for the formation of public opinion, it can be seen that the people of Pekanbaru City really dislike the occurrence of the forest and land fire haze because social, economic, and educational activities of the people of Pekanbaru City are hampered by the forest and forest fire haze in Riau Province in 2019. Regional Disaster Management Agency (BPBD) Province Riau, as the party responsible for handling forest and land fires, has made every effort to put out fires in the field directly, then provided masks, medicines, and health service posts for people affected by the haze, and also made efforts to monitor forest and land fire prevention and control activities. and carry out law enforcement to parties proven to have burned forests and land. Keyword: Public Opinion, Haze, Land and Forest Fire.